Galactomannan Downregulates the Inflammation Responses in Human Macrophages via NFκB2/p100. (9th September 2015) - Toledano, Víctor; Hernández-Jiménez, Enrique; Cubillos-Zapata, Carolina; Flandez, Marta; Álvarez, Enrique; Varela-Serrano, Aníbal; Cantero, Ramón; Valles, Gema; García-Rio, Francisco; López-Collazo, Eduardo
Abstract : We show that galactomannan, a polysaccharide consisting of a mannose backbone with galactose side groups present on the cell wall of several fungi, induces a reprogramming of the inflammatory response in human macrophages through dectin-1 receptor. The nuclear factor kappa-light-chain-enhancer of activated B cells 2 (NF κ B2)/p100 was overexpressed after galactomannan challenge. Knocking down NF κ B2/p100 using small interfering RNA (siRNA) indicated that NF κ B2/p100 expression is a crucial factor in the progression of the galactomannan-induced refractoriness. The data presented in this study could be used as a modulator of inflammatory response in clinical situations where refractory state is required.